Frequency Damping Backpack Exoskeleton with Load Variable Spring Stiffness. Issue 1 (October 2021) - Patil, C R; Vyas, A; Pimpley, A M; Borkar, P S; Thapa, A; Kotwal, G N
Abstract: Heavy backpacks are one of the major reasons for spinal, neck and shoulder related problems. It also affects the human posture in an adverse way. This a major concern among school children, who have to carry heavy textbooks and stationery material. The suspended load backpack is designed to tackle these problems. However the major flaw in these backpacks is the fixed spring constant despite a range of various loads being acted upon it. Furthermore, the current frame is heavy and uses a complex damping technique. In this paper, we make a mechanism to vary the spring stiffness of the backpack according to its payload without having to adjust the damping coefficient. The redesigning of the straps ensures even load distribution during running, jumping, etc. We use a power screw type mechanism coupled with a spring to add preload. We also simulate the model to validate and differentiate between the performances.